PENERAPAN KESELARASAN RANGKAIAN ALUR (NARASI) DAN PENGALAMAN RUANG DALAM PSIKOLOGI ARSITEKTUR - Rafi Mentari; Sarah Aisha; Marselly Dwiputri (Lakar: Jurnal Arsitektur, 2020)
In this increasingly advanced era, there are more and more developments in architectural spaces that provide a variety of experiences for the users. These architectural spaces are generally created from the elements in the form of the surface (floor), the wall (barrier), and the roof (ceiling) which are combined with accessibility for user movement. The purpose of these elements is to fulfill space requirements that can provide a specific experience for the user. These developments are further explored in the article, in term of psychological and its relation to architecture, that the alignment of a series of plot (narrative) and spatial experiences can evoke positive emotions and feelings. This article aims to analyze the processing of a series of plot (narrative) in space so that later alignment can provide a different experience individually by emphasizing the supporting elements.